Comparative genomics of gene families in relation with metabolic pathways for gene candidates highlighting - Larivière, D.; Couvin, D.; Droc, Gaëtan; Lorenzo, G.; Guignon, Valentin; Rouard, M.; Lyons, E.; This, D.; Bocs, S.; Dufayard, Jean-François (2016)
The study of gene families is an important field of comparative genomics, allowing, by the analysis of evolutionary history, to identify homology relationships, gene losses and to help in annotation transfers. The addition of metabolic information improves the identification of candidate genes by addition of functional and gene network data. We propose new web systems to facilitate and improve the analysis of gene family for the search of candidate genes in plants. GenFam )http://genfam.southgreen.fr/) is dedicated to the manual and precise analysis of gene families and includes specific workflows running under a Galaxy platform, allowing to gather several data sources, analysis and visualization tools, in order to (i) build custom families (ii) run analysis workflows dedicated to the analysis of gene families (iii) visualize analysis results and functional evidences through a dedicated visualization dashboard.